Reduced Genome of the Gut Symbiotic Bacterium “Candidatus Benitsuchiphilus tojoi” Provides Insight Into Its Possible Roles in Ecology and Adaptation of the Host Insect - Mondal, Shakhinur Islam; Akter, Arzuba; Koga, Ryuichi; Hosokawa, Takahiro; Dayi, Mehmet; Murase, Kazunori; Tanaka, Ryusei; Shigenobu, Shuji; Fukatsu, Takema; Kikuchi, Taisei (Frontiers in Microbiology, 2020)
Diverse animals, including insects, harbor microbial symbionts within their gut, body cavity, or cells. The subsocial parastrachiid stinkbug Parastrachia japonensis is well-known for its peculiar ecological and behavioral traits, including its prolonged non-feeding diapause period and maternal care of eggs/nymphs in an underground nest. P. japonensis harbors a specific bacterial symbiont within the gut cavity extracellularly, which is vertically inherited through maternal excretion of symbiont-containing white mucus. Thus far, biological roles of the symbiont in the host lifecycle has been little understood. Here we sequenced the genome of the uncultivable gut symbiont “Candidatus Benitsuchiphilus tojoi”. The symbiont has an 804 kb circular chromosome encoding 606 proteins and a 14.5 kb plasmid encoding 13 proteins. Phylogenetic analysis indicated that the bacterium is closely related to other obligate insect symbionts belonging to the Gammaproteobacteria, including Buchnera of aphids and Blochmannia of ants, and the most closely related to Ishikawaella, an extracellular gut symbiont of plataspid stinkbugs. These data suggested that the symbiont genome has evolved like highly reduced gamma-proteobacterial symbiont genomes reported from a variety of insects. The presence of genes involved in biosynthesis pathways for amino acids, vitamins and cofactors in the genome implicated the symbiont as a nutritional mutualist, supplementing essential nutrients to the host. Interestingly, the symbiont’s plasmid encoded genes for thiamine and carotenoid synthesis pathways, suggesting the possibility of additional functions of the symbiont for protecting the host against oxidative stress and DNA damage. Finally, possible involvement of the symbiont in uric acid metabolism during diapause is discussed.